Microwave Imaging Based on Time Reversal Mirror for Multiple Targets Detection - Tong Mu; Yaoliang Song, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Time reversal (TR) is an applicable technique for target detecting and has gained extensive attention due to its self-adaptive focusing ability. However, the imaging performance of the traditional time reversal mirror (TRM) deteriorates in multiple targets cases. A TR imaging approach for multiple targets detection is proposed in this paper. Different from the direct retransmission of the TR signals, the time domain gating is applied to the targets responses to divide them into different groups, and the optimal time frame corresponding to each target which will be utilized in the subsequent step is calculated. After the retransmission of the gated TR signals, the essential zero setting step and the summation step are conducted to construct the imaging function. Numerical simulations are carried out for three multi-targets cases using the finite-different time-domain (FDTD) method. The imaging results are compared with the traditional TRM method and indicate the effectiveness and the superiority of the proposed approach.